And then there were none [videorecording (DVD)] - Viveiros, Craig; Dance, Charles; Turner, Aidan, 1983-; Maxwell Martin, Anna, 1977-; Neill, Sam; Richardson, Miranda; Dermody, Maeve; Gorman, Burn, 1974-; Stephens, Toby, 1969-; Taylor, Noah (Acorn Media, 2016)
As the world teeters on the brink of war, ten strangers are persuaded to retreat from their troubled lives to Soldier Island, an isolated rock near the Devon coast. When a storm cuts them off from the mainland, the true reason for their presence on the island becomes horribly clear: they are to be executed, one by one.